A comprehensive analysis of the performance of thermoelectric generators with constant and variable properties. (1st May 2019) - Chen, Wei-Hsin; Lin, Yi-Xian; Wang, Xiao-Dong; Lin, Yu-Li
Graphical abstract: Highlights: Performances of TEGs with constant/variable materials' properties are studied. Decreasing cold surface temperature with fixed Δ T may intensify or abate the performance. Oscillating hot surface temperature may increase or decrease the performance. Practical performance of a TEG and its deviation from theory depend on properties adopted. Considering variable properties of material provides a more realistic outcome. Abstract: Material properties of a thermoelectric generator play a pivotal role in directly converting heat into electricity. To provide a comprehensive study on power generation of thermoelectric generators, four different materials with constant and temperature-dependent properties are investigated numerically. The influences of the temperature difference across the elements, the temperature at the cold side surface, and the temperature oscillation at the hot side surface on the performance of the generators are simulated numerically and analyzed systematically. The predictions indicate that the output power, temperature-difference square rule, and impedance matching of the materials with the variable properties deviate from the theoretical results with constant properties, but their behavior always obeys the self-consistency. At a given temperature difference, a decrease in the cold surface temperature may intensify or abate the performance, depending on the material properties adopted. Oscillating the hot surface temperature may increase or decrease the output power and efficiency. In summary, the practical performance of a thermoelectric generator and its deviation from the theoretical performance depend strongly on the properties adopted. Therefore, the consideration of the variable properties of materials can provide a more realistic outcome compared to the predictions with constant properties.